2012
DOI: 10.1073/pnas.1212141109
|View full text |Cite
|
Sign up to set email alerts
|

Functional convergence of hopanoids and sterols in membrane ordering

Abstract: Liquid-ordered phases are one of two biochemically active membrane states, which until now were thought to be a unique consequence of the interactions between eukaryotic membrane lipids. The formation of a liquid-ordered phase depends crucially on the ordering properties of sterols. However, it is not known whether this capacity exists in organisms that lack sterols, such as bacteria. We show that diplopterol, the simplest bacterial hopanoid, has similar properties and that hopanoids are bacterial "sterol surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
141
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 43 publications
13
141
0
Order By: Relevance
“…Furthermore, the ΔG ex values for the diplopterollipid A and cholesterol-SM are nearly identical and negative, thus confirming that interactions between both pairs of these lipids are favorable. This finding is consistent with our previous results showing that diplopterol orders lipid A but does not order unsaturated phospholipids (15). Thus, we show that diplopterol interacts favorably only with saturated lipids and that the interactions of diplopterol with lipid A and cholesterol with SM are thermodynamically analogous.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, the ΔG ex values for the diplopterollipid A and cholesterol-SM are nearly identical and negative, thus confirming that interactions between both pairs of these lipids are favorable. This finding is consistent with our previous results showing that diplopterol orders lipid A but does not order unsaturated phospholipids (15). Thus, we show that diplopterol interacts favorably only with saturated lipids and that the interactions of diplopterol with lipid A and cholesterol with SM are thermodynamically analogous.…”
Section: Resultssupporting
confidence: 82%
“…Early investigations showed that both sterols and hopanoids exhibit the ability to condense lipids (13,14). We demonstrated that hopanoids are indeed bacterial sterol surrogates with respect to their ability to form a liquid ordered phase, and that they promote liquid-liquid phase separation in membranes (15). This observation decouples the evolution of ordered biochemically active liquid membranes from the requirement for molecular oxygen and suggests that the ability to subcompartmentalize membranes could have preceded the evolution of sterols.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Using a combination of deuterium NMR spectroscopy on multilamellar lipid-sterol systems in combination with Monte Carlo simulations of microscopic models of lipid-sterol interactions, Mouritsen and coworkers [88] concluded that the evolution in the molecular chemistry from lanosterol to cholesterol is manifested in the increase in the ability of the sterols to promote and stabilize lipid order, in the form of the Lo phase in model phospholipid-sterol membranes. However, experimental work using the simplest of bacterial sterol surrogates, the hopanoid diplopterol, demonstrated that this property was also present in bacteria early in evolution [117,118]. The second requirement, i.e.…”
Section: Fj Barrantes / Cholesterol-receptor Interactionsmentioning
confidence: 99%